Social Impacts of Hosting the 2022 FIFA World Cup on Citizens and Residents in Qatar - Rashid Al Gheithi; Abdul Rahim Al Droushi; Amin Gaafar (College of Physical Education and Sport Sciences, 2024)
This study aimed to identify the social impacts of hosting the 2022 FIFA World Cup in Qatar on its citizens and residents. Also, it aimed to reveal the differences in these impacts across various demographic variables, including identity, age group, and gender. The researcher adopted a descriptive methodology to achieve these objectives, collecting data mainly through a questionnaire administered to a diverse sample of 411 individuals who willingly participated in the study. The study's findings unveiled a range of significant social effects from this momentous event hosted in Qatar. Notably, these effects manifested in improving the country's image, fostering an incomparable sense of community pride, developing a heightened feeling of belonging, and arousing an overwhelming enthusiasm within the populace in Qatar towards hosting such grand-scale sporting events. Moreover, the World Cup fostered stronger feelings of security and social cohesion. Based on these results, the study advocates recommendations for future investigative endeavors. Despite its significant results, the study recommends future research to encompass a more diverse and inclusive representation from various regions. This is crucial to understand better the social outcomes of large-scale sporting events among the population.